Effects of Attention on Visible and Invisible Adapters. (June 2014) - Jung, Yaelan; Chong, Sang Chul
It has been shown that attention can modulate the processing of a stimulus, even when it is invisible (Bahrami, Carmel, Walsh, Rees, & Lavie, 2008, Perception, 37, 1520–1528). Previous studies, however, investigated the effect of spatial attention on the processing of only invisible items. Thus, it remains unclear how the effect of spatial attention is distributed over visible and invisible items when these items are simultaneously attended at the same location. In the present study we addressed this question using two types of adapters, one visible and one invisible, and compared how attention affected the processing of each adapter. Moving gratings and tilted gratings were presented to each eye; the moving ones were dominant over the tilted ones. Both types of stimuli were located on the left and right sides of a fixation cross, and the participants performed a task that modulated their attention to one side or the other. In experiment 1 they were asked to detect the contrast decrement of one of the moving gratings, and in experiment 2 they detected a dot that was presented to both eyes. We found that attention increased the amount of motion aftereffects induced by the visible adapters. However, we did not find effects of attention on tilt aftereffects from the invisible adapters. Finally, in experiment 3 we found that attention successfully increased the amount of tilt aftereffects when the adapters were not suppressed. These findings suggest that spatial attention is more likely to influence visible items than invisible items in the same location. We also found that invisible items do not interfere with the attentional modulation of the processing of visible items.